The impact of Instagram influencer marketing in the restaurant industry - Anjos, Catarina Jorge da Fonseca (2021)
In Portugal, the restaurant market has been increasingly growing and thus, in order to differentiate themselves from the competition, restaurants should try to provide their consumers with the best experience possible. However, when improving their offer, they should also communicate it and draw the attention of the public, taking advantage of all available means of communication and opting for the most effective marketing techniques. Therefore, the main objective of this dissertation is to study the six dimensions that encompass a set of digital influencers’ characteristics and to understand if this is actually a communication channel that positively impacts the Portuguese restaurant sector. In order to draw relevant conclusions, a research model based on the study hypotheses was developed, after a detailed literature review was carried out where several concepts, data and theories from all over the world related to the topic in question were explored. On the other hand, a survey was also conducted which obtained 395 valid answers, as well as a focus group in which 6 individuals participated. Finally, after analysing all the information gathered, it was concluded that of the six dimensions of the research model, only one has no impact on the increase of potential clients in restoration. In this way, the remaining five are considered to be sufficiently differentiating to arouse consumer interest in visiting restaurants promoted by Instagram influencers.